Inventory for technical-technological systems. Polluters of surface waters - Grizo, Aleksandar (Macedonian Journal of Ecology and Environment, 1996)
Although in the water law of the Republic of Macedonia, from 1981, has foreseen the organization of an inventory of polluters and pollutants of surface waters, so far this has not been done. In the present article there are pointed out the efforts undertaken in the developed countries in organizing a monitoring system, and the need of organizing an inventory of pollutants of surface waters, in the Republic of Macedonia, as a part of the general monitoring system of the country. The main principles of organizing the inventory are proposed.